Mahzab Sunan Kalijaga (Refleksi Setengah Abad Genealogi Epistemologi Studi Ilmu Hukum Islam Integratif di Fakultas Syariah dan Hukum UIN Sunan Kalijaga: 1963-2013) - Waryani Fajar Riyanto (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
The title above, exactly as the title of the book that has been preparedby the writer to welcome half century (50 years) of the age of Faculty of Syariahand Law UIN Sunan Kalijaga: 1963-2013, which may God willing, will be launchedin the middle of 2014. Here the author deliberately uses the term Mazhab SunanKalijaga, to summarize the four types of epistemology nodes that have ever beenflourished in the FSH, namely: Indonesian Fiqh, Indonesianizing of IndonesianFiqh, Mazhab Jogja, and Integration-Interconnection. By the historical, critical,and analytical approaches, this initial study is expected to provide enlightenmentand the making smart effort of history for FSH.